Ear protective devices-the state of the art - Geetha Mukundan and Malini M. S (Journal of All India Institute of Speech and Hearing, 1970)
In this paper, an attempt is made to describe the various types of ear protective devices and to discuss their merits and demerits. Themethods of evaluating the effectiveness of ear protective devices are also described. Suggestions are given for motivating the workers to use thesedevices.